PROGRAM PEMETAAN LAHAN KRITIS DENGAN REMOTE SENSING UNTUK KEWASPADAAN BAJIR DAN TANAH LONGSOR AKIBAT PERUBAHAN FUNGSI LAHAN DI DAERAH MANDALIKA - Yadnya, Made Sutha; Kanata, Bulkis; Zainuddin, Abdullah; Paniran, Paniran; Ramadhani, Cipta; Rosmaliati , Rosmaliati (Jurnal Pepadu, 2024)
Lecturers' empathy in implementing the Tri Dharma of Higher Education is to provide community service against the dangers of landslides by changing the function of land from hills to landfill. Mataram University has an observatory in Rembitan, part of the Geomagnetic Science and Technology Excellence Center (PUI), which measures the earth's magnetism with the nTesla (Nano Tesla) earth magnetic unit. The measurement results show an anomaly (a decrease in the earth's magnetic value. This is a precursor to an earthquake. Sade and Rembitan villages are one area that must be protected and provide knowledge about the dangers of floods and landslides due to extreme weather. The process of using remote sensing with photos air. The results have been obtained from several disaster-prone points. The women's group in Sade Village has agreed to create a reforestation group to mitigate disasters.